Designing a Cross-Course Project-Based Learning Model in Vocational Higher Education Context - Isnaini Nur Safitri; Mariana Ulfah Hoesny; Pritantina Yuni Lestari (Institut Agama Islam Negeri (IAIN) Manado, 2026)
Developing A Project-based Learning Model Across Two ESP Courses Research paper: English for Specific Purposes (ESP) is an approach to teaching English for specific purposes, whether for academic or professional purposes. One characteristic of ESP learning is learner-centeredness, where students are directly involved in the teaching and learning process. One method that characterizes learner-centeredness is Project-Based Learning (PBL). PBL in ESP courses has often been implemented in the English for Tourism Industry (BIIP) Study Program. However, few project-based learning model has been developed, especially for integrated courses (English for E-tourism and Content and Creative Writing in Tourism). Therefore, this study aims to develop a project-based learning model for integrated courses within the ESP context. This research is a Design and Development Research (DDR) using the ADDIE model. This research was conducted in fifth semester students of the D4 BIIP study program at State Polytechnic of Malang. Observations, literature reviews, and questionnaires were used as data collection methods. Data obtained were analysed using descriptive qualitative method. The result of this study is a project-based learning model for integrated courses. Validation and questionnaire results indicate that the InPro- ESP learning model is feasible with minor suggestion. This model will later be able to be used for implementing learning both in the D4 BIIP Study Program, D4 BIKBP, or other study programs both at Polinema and outside Polinema.Keywords: Project-based Learning model, English for Specific Purposes, Vocational Higher Education